The Lord of the Bacteria: The Fellowship of the Leader and Other Serine Protease Inhibitors - Burchacka, Ewa; Sieńczyk, Marcin (Current Pharmaceutical Design, 2018)
Since antibiotics use is currently limited due to undesired side effects and the increasing antibiotic resistance of various bacteria strains, there is a pressing need to develop new strategies and methods preventing epidemic outbreaks. The virulent potency of bacteria relies on a number of different extracellularly secreted factors among which proteases considered as promising, novel drug targets are of special interest. The first evidence that bacterial cysteine, serine and metalloproteinases contributed to the progression of infection was found in the early 70's. This extracellular proteolytic system allows bacteria to penetrate into tissues, escape detection by the host's immune mechanisms and grow despite limited access to nutrition. A molecule able to selectively inhibit the activity of bacterial proteases in the spread of infection may lead to designing novel therapeutics. Moreover, due to their mechanism of action, bacterial protease inhibitors can be used to fight antibiotic-resistant strains. Herein, we undertake a review of various bacterial proteases together with the design and development of their inhibitors (excluding β-lactams) for the last ten years, and introduce the reader to a brief history of the subject.
Keywords: potential antibiotics